Anticoagulation in Critically Ill Adults during Extracorporeal Circulation - Buchtele, Nina; Staudinger, Thomas; Schäfer, Anne-Kristin; Bögl, Magdalena Sophie; Schoergenhofer, Christian; Schwameis, Michael (Hämostaseologie, 2021)
Extracorporeal circuits including renal replacement therapy, extracorporeal membrane oxygenation, and ventricular assist devices are increasingly used in critically ill patients. The need for anticoagulation to provide circuit patency and avoid thrombosis remains a challenging task for treating physicians. In the presence of overall low scientific evidence concerning the optimal anticoagulants, monitoring tests, and therapeutic target ranges, recommendations are largely expert opinions and most centers use individual “in-house” anticoagulation protocols. This review gives a practical view on current concepts of anticoagulation strategies in patients with extracorporeal assist devices.
Keywords: anticoagulants; blood coagulation tests; continuous renal replacement therapy; extracorporeal membrane oxygenation; heart-assist devices